I Feel Less Blue When I Read With You: The Effect of Reading Aloud With a Child on Adult Readers’ Affect - Rabinowitz, Sara; Pavlov, Christina; Mireku, Brianna; Ying, Katrina; Zhang, Jiaqi; Read, Kirsten (Frontiers in Psychology, 2021)
This study examined the potential benefits of shared reading with a child on adult readers’ mood. In two experiments, young adults were randomly assigned to either read storybooks with a child or to read the same books aloud alone. In both experiments, readers experienced more positive emotions than those who read the story aloud alone. In Experiment 1, the level of interactivity between the reader and child also positively correlated with readers’ experience of positive emotions. In Experiment 2 participants who read with a child aligned their own book preferences with those of the child. Overall, participants preferred the longer and more complex storybook as it gave more opportunities for the reader and child to interact. These findings support the hypothesis that simple read-aloud experiences are not only positive for children, but have the potential to also positively impact the mood of adult readers who share books with a child.